2022
DOI: 10.1002/smtd.202200181
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Step Solid‐State Scalable Transformation of Ni‐Based Substrates to High‐Oxidation State Nickel Sulfide Nanoplate Arrays as Exceptional Bifunctional Electrocatalyst for Overall Water Splitting

Abstract: Hydrogen, undoubtedly the next‐generation fuel for supplying the world's energy demands, needs economically scalable bifunctional electrocatalysts for its sustainable production. Non‐noble transition metal‐based electrocatalysts are considered an economic solution for water splitting applications. A single‐step solid‐state approach for the economically scalable transformation of Ni‐based substrates into single‐crystalline nickel sulfide nanoplate arrays is developed. X‐ray diffraction and transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The choice of the electrocatalyst was based on previous literature reports, where earth-abundant nickel-based materials were successfully demonstrated as effective bifunctional catalysts for overall water splitting. [21,41] Thus, Ni foil substrates were transformed into electrocatalytic, binder-free electrodes via a welloptimized single-step transformation process, as detailed in the experimental section. The NiS 2 pS x surface catalyst is prepared by the direct in situ transformation of Ni foil under elemental sulfur environments in the ratio (2:1).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of the electrocatalyst was based on previous literature reports, where earth-abundant nickel-based materials were successfully demonstrated as effective bifunctional catalysts for overall water splitting. [21,41] Thus, Ni foil substrates were transformed into electrocatalytic, binder-free electrodes via a welloptimized single-step transformation process, as detailed in the experimental section. The NiS 2 pS x surface catalyst is prepared by the direct in situ transformation of Ni foil under elemental sulfur environments in the ratio (2:1).…”
Section: Resultsmentioning
confidence: 99%
“…Although their HER and OER performances are excellent, their large-scale industrial application is greatly limited by their inherent scarcity and high costs. 6,7 To address these challenges, a variety of cost-effective transition metal-based electrocatalysts with favourable activity for the OER or HER, such as metal oxides, 8,9 sulfides, 10,11 selenides, 12,13 nitrides 14,15 and phosphides, 16,17 have been developed. Dual-functional catalysts capable of catalyzing both the HER and the OER simultaneously are being explored to simplify the water splitting systems.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal chemicals (TMCs) have been widely used in research as catalysts targeting HER/OER due to their abundant resource storage, low cost, and environmental friendliness, especially nickel-based materials. However, it was found that their low intrinsic conductivity is a huge obstacle to overcome to replace the precious metal HER/OER catalysts, . Nowadays, the main methods for the preparation of Ni-based catalysts are the hydrothermal method, the sol–gel method, the vapor-phase deposition method, the chemical method, and the electrodeposition method. , The hydrothermal method requires more stringent preparation conditions.…”
Section: Introductionmentioning
confidence: 99%